The Ugandan Health Systems Reforms: miracle or mirage? - Yates, Rob; Tashobya, Christine Kirunga; Ssengooba, Freddie; Murindwa, Grace; Lochoro, Peter; Bataringaya, Juliet; Nazerali, Hanif; Omaswa, Francis (My University, 2006)
Poor health indicators in the 1990s prompted the Government of Uganda and development partners to embark, at the turn of the century, on an extensive programme of health systems reforms to improve sector performance. With only a modest increase in resources, these reforms have resulted in large increases in outputs for ambulatory services. Out-patient attendances and immunisation rates have doubled. Furthermore, the growth in consumption of these services appears to be highest for the poorest socio-economic groups. However, statistics for key in-patient services, most noticeably maternity services, remain virtually unchanged. This chapter attempts to assess the significance of these changes. Is it a miracle of improved efficiency or a mirage unlikely to lead to improved health outcomes? We try to identify the key reforms within health and across government, which may be responsible for the changes in output performance. A number of supply side reforms that have have increased the availability of essential inputs are highlighted. In addition, a major demand side policy (abolishing user fees) had a significant impact on the consumption of services. We conclude that increased utilisation of ambulatory services does signify improvements in consumer welfare and therefore health sector performance. However, stagnant maternity outputs indicate that key in-patient services are still not meeting the expectations of the population. Only reliable outcome data will resolve the debate about the significance of the changes in output indicators. Further research will also be required to disentangle the relative impact of the different components of the reforms.
Keywords: Health systems reforms; Miracle; Mirage